Innovation systems performance drivers and outputs: a systematic literature review and directions for future research - Alvarez, Ana Maria Ortega (2024)
Innovation is a requirement to tackle social, economic and environmental challenges. Understanding how to measure innovation is important for policymakers, business and social leaders, as it allows the design of better strategies related to the development and evaluation of innovation systems (ISs). The purpose of this systematic literature review (SLR) is to identify and explain the key innovation system performance (ISP) drivers and outputs through descriptive and content analyses. A total of 139 articles between 1998 and 2021 were included in the SLR, and the analyses were performed using software for qualitative research data analysis. The main conclusions are that while research about ISP is increasing, there is little consensus on how to measure innovation drivers and outputs. Future research should address composite and standardised indicators to measure ISP, allowing a better understanding of performance and comparisons among different ISs.